Migration of The Bugis in Bapeang Village Of East Kotawaringin, 1977-2020 (Historical Review of Social Change Perspective) - Ekawati, Nadia Ainur; Erawati, Desi; ., Suryanti (Syams, 2022)
The Bapeang Bugis is a community living in Bapeang village, Mentawa Baru district, Ketapang, East Kotawaringin Regency, Central Kalimantan Province. The Bugis migration took place in the early half of the 20th century, a migration on a large scale caused by the outbreak of the Bone war in 1908 and the DI/TII Kahar Muzakkar rebellion. The dominance of the Bugis in the religious, cultural, and economic sectors is due to their ability to adapt to other communities, especially with the Banjarese as the original inhabitants of Kalimantan. The Bugis has a number of advantages in the fields of agriculture, fisheries, maritime affairs, and trade, and has a high work ethic stemming from the cultural values of siri na pesse (self-respect and compassion) and other Bugis life philosophies.